2007
DOI: 10.1071/en07021
|View full text |Cite
|
Sign up to set email alerts
|

Omnipresence of biological material in the atmosphere

Abstract: Environmental context. Atmospheric biological particles have been largely overlooked in the past. While some microorganisms have been studied, the majority of other biological particles have not. The presence of these particles might force us to view the atmospheric aerosol differently. Abstract. Measurements of biological particles in the atmosphere during the last decade indicate that the presence of these particles seems to have been underestimated by atmospheric scientists. On the average these primary aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 25 publications
3
66
0
Order By: Relevance
“…For example, observations of particles with radius greater than 0.2 µm between 2000 and 2008 in Mainz, Germany, found that between 5 and 50 % of particle volume was composed of primary biological aerosol particles; at Lake Baikal, Russia, an average of ca. 20 % of particles was observed to be PBAP (by number and volume; particles with radius > 0.2 µm) (Jaenicke et al, 2007). Measurements in the Amazon rainforest found that 40 % of submicron and up to 80 % of supermicron particles were primary biological particles (Graham et al, 2003).…”
Section: S M Burrows Et Al: Impact Of Particle Characteristics On mentioning
confidence: 99%
“…For example, observations of particles with radius greater than 0.2 µm between 2000 and 2008 in Mainz, Germany, found that between 5 and 50 % of particle volume was composed of primary biological aerosol particles; at Lake Baikal, Russia, an average of ca. 20 % of particles was observed to be PBAP (by number and volume; particles with radius > 0.2 µm) (Jaenicke et al, 2007). Measurements in the Amazon rainforest found that 40 % of submicron and up to 80 % of supermicron particles were primary biological particles (Graham et al, 2003).…”
Section: S M Burrows Et Al: Impact Of Particle Characteristics On mentioning
confidence: 99%
“…Because of the mixing of biomaterials with nonbiomaterials in the atmosphere, or in soils or water (from which aerosols may be generated), a significant fraction of aerosols are complex mixtures of biological and nonbiological materials. Some measurements of proteins in aerosol particles indicate that around 20% of atmospheric airborne particles contain significant amounts of protein (9,10), although most measurements of individual aerosols do not look for protein as one of the molecular types.…”
Section: Bioaerosols and Other Organic Carbon Aerosolsmentioning
confidence: 99%
“…Airborne biological particles (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) are important in the transmission of diseases (11,12) of humans (e.g., tuberculosis, influenza), farm animals (e.g., coccidioidomycosis, anthrax), agricultural crops (e.g., black stem rust), and trees (e.g., white pine blister rust). Airborne pollens and proteins shed from household pets can cause allergies.…”
Section: Bioaerosols and Other Organic Carbon Aerosolsmentioning
confidence: 99%
“…The share of atmospheric aerosol composition belonging to PBAP is large and possibly underestimated (Jaenicke et al, 2007), but is also very uncertain. Estimates of relative PBAP fraction from global models and local measurements reveal large differences between reports.…”
Section: Introductionmentioning
confidence: 99%